The effectivity of the Sangguniang Kabataan (SK) in empowering the youth through public policy making in the municipality of Tibiao (1996-2002) - Begaso, Dianna Fe Y. (2003.)
This study aims to discuss the effectivity of the Sangguniang Kabataan in empowering the youth through public policy making in the Municipality of Tibiao, Antique (1996-2002)., The objectives of the research include the identification of the programs and activities initiated by the six (6) SK Chairperson and the Federation President during their six-year term and to discuss their performance as local legislators. Through this, the researcher may ascertain whether the SK in the Municipality of Tibiao is effective in empowering the youth through public policy making. The respondents in the research include the members of the Sangguniang Bayan of the municipality composed of the vice mayor and eight (8) legislative members and the Association of Barangay Council (ABC) president and all the members of the Sangguniang Barangay composing of the Barangay Captain and the seven (7) council members. The instrument used in this study is an open-ended questionnaires divided into two major parts: (a)activities and programs of the SK in the intellectual, political and economic, social and cultural, moral and spiritual, and physical aspects, (b)the performance of the SK concerned as local legislators. The discussion of the legislative performance of the 6 SK Chairpersons and the Federation President is limited to the perception of the Barangay and Municipal legislative Councils. The major findings of the research are primarily based on written responses of the respondents mentioned. The researcher found out that in the six-year term (1996-2002) of the SK concerned, their effectiveness focused mainly in the socio-cultural and physical aspects. participation of the youth in the making of public policy is poor and inactive. As legislators, they initiated a limited number of resolutions constituting to their ineffectiveness. There were three reasons that had identified by the researcher, which hampered the SK performance, namely: academic obligations in school, lack of coordination among members (weak organization), and limited support from the Barangay and Municipal Legislative Councils. In general, the six(6) SK Chairpersons and the Federation President in the Municipality of Tibiao, antique is ineffective in bringing empowerment to their constituents through public-policy.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Sangguniang Kabataan -- Tibiao,Antique -- 1996-2002.